Sex differences in the association between the uric acid to high density lipoprotein cholesterol ratio and mild cognitive impairment in patients with type 2 diabetes mellitus - Chu, Yafen; Wang, Li; Guo, Qiannan; Chang, Yu; Lu, Ni; Gao, Qingyue; Song, Zhibang; Xu, Linlin; Wang, Jumei; Chen, Yan; Ding, Li; Song, Bing (Frontiers in Nutrition, 2025)
AimUric acid to high density lipoprotein cholesterol ratio (UA/HDL-c) related to nutrient metabolism disorder is associated with the onset of diabetic complications including mild cognitive impairment (MCI). However, the relationship between UA/HDL-c and MCI in type 2 diabetes mellitus (T2DM) patients with different gender remains unclear. Therefore, this study aims to explore the association between UA/HDL-c and MCI in female and male patients with T2DM.MethodsA total of 223 patients were stratified into either the control or the MCI group based on the presence or absence of MCI. Comparative analyses of clinical parameters were conducted, and the associations between UA/HDL-c and cognitive function were assessed across all patients as well as within female and male subgroups. Binary logistic regression was employed to identify independent risk factors for MCI in female and male patients with T2DM.ResultsCompared to the 137 participants without MCI, the 86 individuals with MCI exhibited significantly higher levels of UA/HDL-c. Higher UA/HDL-c levels were associated with lower scores on the Montreal Cognitive Assessment, which reflects global cognitive function, as well as with poorer performance on the Verbal Fluency Test and the Clock Drawing Test, which reflect executive and visuospatial functions in female patients, respectively. These associations were not observed in male patients. Furthermore, binary logistic regression analysis indicated that elevated UA/HDL-c levels were a risk factor for MCI in women, regardless of adjustments for age, duration of diabetes mellitus, and duration of hypertension.ConclusionElevated UA/HDL-c levels are not only associated with overall cognitive function in female patients with T2DM, but also specifically linked to impairments in executive function and visuospatial abilities. However, this association is not observed in male patients. Among women with T2DM, elevated UA/HDL-c levels serve as an independent risk factor for the development of MCI. These findings suggest a sex-specific relationship between UA/HDL-c levels and cognitive dysfunction.